The machinery of healthy vasodilatation: an overview - Pourová, Jana; Dias, Patrícia; Pour, Milan; Mladěnka, Přemysl (Pflugers Archiv, 2025)
Cardiovascular function depends on an adequate vascular tone facilitating appropriate blood flow to individual tissues according to their needs. The tone results from the interplay between vasodilatation and vasoconstriction. Its rapid and efficient regulation is secured by many interconnected physiological mechanisms, both at the level of the vascular smooth muscle and the endothelium. The purpose of this review is to provide an update of the current knowledge on the mechanisms of physiological vasodilatation. First, two principal intracellular signaling pathways linked to the activation of protein kinases PKA and PKG are introduced. Subsequently, the role of endothelium-derived relaxing factors together with the endothelium-dependent hyperpolarization is discussed. The roles of ion channels and gap junctions in the communication between endothelium and vascular smooth muscle cells are particularly discussed. Finally, principal vasodilatory stimuli (mechanical, thermal, chemical) and their mechanisms of action are briefly introduced.
Keywords: Muscle, Smooth, Vascular; NO; PKG; vazodilatace; cévní endotel; Vasodilatation; PKA; signální transdukce; EDRF; Gap Junctions; iontové kanály; proteinkinasy závislé na cyklickém GMP; Endothelium, Vascular; Cyclic GMP-Dependent Protein Kinases; Signal Transduction; Cyclic AMP-Dependent Protein Kinases; Vasodilation; Ion Channels; Animals; lidé; svaly hladké cévní; Humans; zvířata; proteinkinasy závislé na cyklickém AMP; mezerový spoj